The Development of Study Skill Tools in Evaluating Student's Study Orientation Skills and Its Relationship towards Academic Performance - Mohd. Ghani, Awang; Suriya Kumar, Sinnadurai (Academy Publisher, 2011)
Abstract—The purpose of this study is to measure the study orientation skills and to provide remedial devices in correcting respondents’ study orientation skills mistakes. The study reveals the relationship between study orientation skills and the grade point average. In addition, the classification of group achiever based on study orientation skills is identified into higher group achiever, normal group achiever and under-achiever. The remedial devices used comprise of the web-based adapted version of Study Habits and Attitudes (SSHA) questionnaires on http://survey.ump.edu.my/surveyor and http://survey.ump.edu.my/admin. Other remedial devices used are study orientation skills module, kit; Ghani’s format of note-taking, DVD’s and study orientation skills classes. 59 respondents were selected as the sample of study by group sampling from the Faculty of Computer System & Software Engineering and 59 respondents from the Faculty of Civil Engineering & Natural Resources. The research applies Quasi-experimental pre-test and post-test separated group design. The respondent’s study orientation skills are analyzed and sorted into three groups of achievement; the higher achiever, normal achiever and under achiever. The significant difference test on study orientation skills was conducted based on pre-test and post-test mean score and the significant differences test on the academic performance was done based on grade point average scores in semester 1 and 2 of first year students. The significant difference test used paired t-test based on statistical package of social science computer program. r Pearson product-moment correlation of coefficient results will show the relationship between study orientation skills and grade point average for each group and between the groups. The internal consistency reliability of the remedial devices is measured by Cronbach’s alpha score. Results obtained shows that there is a significant difference between pre-test and post test for study orientation skills for Civil Engineering & Natural Resources respondents (t = 8.47, p = 0.000) and Computer System & Software Engineering (t = 2.74, p = 0.008). Significant difference results are also shown by grade point average for both tested groups (t = 3.054, p = 0.003) and (t = 3.187, p = 0.002). A significant correlation was found on the relationship between study orientation skills and grade point average for each tested group, based on r value was 0.24 (p = 0.05) for Civil Engineering & Natural Resources and r was 0.33 (p = 0.05) for Computer System and Software Engineering. The correlation between both groups tested for study orientation skills and grade point average are r = 0.16 (p = 0.05), r = 0.15 (p = 0.05), r = 0.13 (0.05) and r = 0.31 (p = 0.01). Index Terms—study orientation skills, study habits, study attitudes, academic performance